A study to assess anemia and hypoalbuminemia in diabetic patients with ulcers - M., Devaprashanth; Ramesh, B. S.; Kumar, Pushpa Satish (International Surgery Journal, 2021)
Background: Diabetic foot is a severe public health issue. Nutrition is important in the repair of soft tissue injuries and wound healing and specific nutrients have been shown to enhance wound healing. Anemia and hypoalbuminemia are among the commonly encountered deficiencies in patients. Early detection of nutritional deficiencies and their prompt treatment is imperative for the effective management of diabetic foot ulcers. The aim of the study was to investigate the prevalence of anemia and hypoalbuminemia in diabetic foot patients presenting at our institution. Methods: Hemoglobin and albumin levels of 175 patients with diabetic foot were collected. Data was tabulated and analysed with descriptive statistics. Results: Hemoglobin varied from 6.5 g/dl to15 g/dl (10.5±2.3 g/dl). 116 (66.28%) patients had anemia. Among the 66 female patients, 43 (65.15%) had anemia. Among the 109 male patients, 73 (66.97%) had anemia. 11 of the 29 patients aged less than 40 had anemia (37.93%), while 105 of the 146 (71.91%) patients above 40 years had anemia. Albumin levels ranged from 1.6 g/dl to 5.4 g/dl (3.3±1.06 g/dl). 93 (53.14%) patients had hypoalbuminemia. 33 of the 66 female patients (50%) had hypoalbuminemia. 60 (55.04%) of the 109 male patients had hypoalbuminemia. 4 of the 29 (13.79%) patients below 40 years had hypoalbuminemia 89 of the 146 patients (60.9%) above 40 years had hypoalbuminemia. Conclusions: Anemia and hypoalbuminemia are common in patients with diabetic foot ulcers, with males being more commonly affected by both than females and older age group being more commonly affected than younger age group.